Symposium 3: Intercultural e-learning: Reflections on Developing a Collaborative Approach to Pedagogy and Educational Technology in a Sino–UK Context - Banks, Sheena; Lally, Vic; Bangxiang, Liu; McConnell, David (Proceedings of the International Conference on Networked Learning, 2006)
This paper focuses on the processes of ‘intercultural’ collaboration in the development of eLearning materials for the eChina UK programme